Procrastinación académica en adolescentes del Perú: Revisión sistemática de factores emocionales, sociales y familiares - Hernández Aparcana, Jesús Yandir (2026)
Academic procrastination in adolescents is a phenomenon that negatively affects their academic performance. In the Peruvian context, emotional, social, and family factors play a crucial role in this behavior. However, there are few studies that address this phenomenon from a comprehensive perspective in this specific context. The objective of this work was to analyze the theoretical models that explain academic procrastination in Peruvian adolescents and its relationship with emotional, social, and family factors. A systematic review of the literature was carried out, following the PRISMA guidelines. Studies published between 2019 and 2024 were selected, in Spanish and English, from databases such as Scopus, Scielo, Redalyc, and Google Scholar. In total, seven studies were included. The studies indicate that academic procrastination in Peruvian adolescents is influenced by various factors such as low emotional self-regulation, lack of motivation, social and family pressure. Academic procrastination is a multifactorial phenomenon that should not be considered only as a problem of disorganization.